Limit and Geometry 001

Calculus Level 3

There is a quarter circle O A B \rm OAB inscribed in a unit circle as shown in the diagram. Let P \rm P be a point on arc A B \rm AB that satisfies P O A = θ \angle \rm POA = \theta , and r ( θ ) r(\theta) be the radius of the circle that is tangent to arc A B \rm AB at point P \rm P and also internally tangent to the unit circle.

What is the value of the limit lim θ 0 + r ( θ ) θ \lim \limits_{\theta \to 0^+} \dfrac{r(\theta)}{\theta} ?

2 2 2 \sqrt{2} 2 \sqrt{2} 2 + 1 \sqrt{2}+1 2 1 \sqrt{2}-1 2 2 2-\sqrt{2}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

형준 유
Oct 1, 2020

Let O 1 \rm O_1 be the center of the unit circle and let O 2 \rm O_2 be the center of the circle of radius r ( θ ) r(\theta) .

O O 1 = 1 \overline{\rm OO_1}=1 , O O 2 = 2 + r \overline{\rm OO_2}=\sqrt{2}+r , O 1 O 2 = 1 r \overline{\rm O_1O_2}=1-r

O 1 O O 2 = O 1 O A P O A = π 4 θ \angle \rm O_1 O O_2=\angle \rm O_1 O A-\angle \rm P O A=\dfrac{\pi}{4}-\theta

Apply cosine rule to triangle O O 1 O 2 \rm O O_1 O_2 , and we get the following equation.

O 1 O 2 2 = O O 1 2 + O O 2 2 2 O O 1 × O O 2 cos ( O 1 O O 2 ) {\overline{\rm O_1O_2}}^2={\overline{\rm OO_1}}^2+{\overline{\rm OO_2}}^2-2{\overline{\rm OO_1}} \times {\overline{\rm OO_2}} \cos \left(\angle \rm O_1 O O_2\right)

( 1 r ) 2 = 1 + ( 2 + r ) 2 2 ( 2 + r ) cos ( π 4 θ ) \Rightarrow \left(1-r\right)^2=1+\left(\sqrt{2}+r\right)^2-2 \left(\sqrt{2}+r\right) \cos \left(\dfrac{\pi}{4}-\theta\right)

r ( θ ) = 2 cos ( π 4 θ ) 1 2 + 1 cos ( π 4 θ ) = cos θ + sin θ 1 2 + 1 cos ( π 4 θ ) \Rightarrow r(\theta)=\dfrac{\sqrt{2} \cos\left(\dfrac{\pi}{4} - \theta \right)-1}{\sqrt{2}+1-\cos\left(\dfrac{\pi}{4} - \theta \right)}=\dfrac{\cos \theta + \sin \theta -1}{\sqrt{2}+1-\cos\left(\dfrac{\pi}{4} - \theta \right)}

(Angle sum identity was used in the last equality.)

Now we can evaluate the limit.

lim θ 0 + r ( θ ) θ = lim θ 0 + ( sin θ θ + cos θ 1 θ ) × lim θ 0 + 1 2 + 1 cos ( π 4 θ ) \lim \limits_{\theta \to 0^+} \dfrac{r(\theta)}{\theta} = \lim \limits_{\theta \to 0^+} \left(\dfrac{\sin \theta}{\theta}+\dfrac{\cos \theta -1}{\theta}\right) \times \lim \limits_{\theta \to 0^+} \dfrac{1}{\sqrt{2}+1-\cos \left(\dfrac{\pi}{4}-\theta\right)}

= ( 1 + 0 ) × 1 2 2 + 1 = 2 2 =\left(1+0\right) \times \dfrac{1}{\frac{\sqrt2}{2}+1}=2-\sqrt{2}

Chew-Seong Cheong
Sep 30, 2020

Let O O be the origin ( 0 , 0 ) (0,0) of the x y xy -plane. Then O A OA and O B OB are two sides of the square inscribed in the unit circle. Since A B = 2 AB=2 , O A = O B = 2 = O P OA=OB=\sqrt 2=OP . The center of the unit circle is Q ( 1 2 , 1 2 ) Q\left(\frac 1{\sqrt 2}, \frac 1{\sqrt 2} \right) . Let the center of the circle tangent to the arc A B AB and unit circle be R R . Then O R = O P + P R = 2 + r ( θ ) OR=OP+PR = \sqrt 2 + r(\theta) and R ( ( 2 + r ) cos θ , ( 2 + r ) sin θ ) R((\sqrt 2 + r)\cos \theta, (\sqrt 2+r)\sin \theta) . We note that Q S = 1 QS=1 since it is a radius of the unit circle. Then Q R = Q S R S = 1 r ( θ ) QR = QS-RS = 1 - r(\theta) . By Pythagorean theorem :

( ( 2 + r ) cos θ 1 2 ) 2 + ( ( 2 + r ) cos θ 1 2 ) 2 = ( 1 r ) 2 ( 2 + r ) 2 2 ( 2 + r ) ( sin θ + cos θ ) + 1 = r 2 2 r + 1 r 2 + 2 2 r + 2 2 ( 2 + r ) sin ( θ + π 4 ) = r 2 2 r ( 2 + 1 sin ( θ + π 4 ) ) r = 2 sin ( θ + π 4 ) 1 r ( θ ) = 2 sin ( θ + π 4 ) 1 2 + 1 sin ( θ + π 4 ) \begin{aligned} \left((\sqrt 2+r)\cos \theta - \frac 1{\sqrt 2} \right)^2 + \left((\sqrt 2+r)\cos \theta - \frac 1{\sqrt 2} \right)^2 & = (1-r)^2 \\ (\sqrt 2+r)^2 - \sqrt 2 (\sqrt 2+r)(\sin \theta + \cos \theta) + 1 & = r^2 - 2r + 1 \\ r^2 + 2\sqrt 2 r + 2 - 2(\sqrt 2+r)\sin \left(\theta + \frac \pi 4 \right) & = r^2 - 2r \\ \left(\sqrt 2 + 1 - \sin \left(\theta + \frac \pi 4 \right)\right)r & = \sqrt 2 \sin \left(\theta + \frac \pi 4 \right) - 1 \\ \implies r(\theta) & = \frac {\sqrt 2 \sin \left(\theta + \frac \pi 4 \right)-1}{\sqrt 2 + 1 - \sin \left(\theta + \frac \pi 4 \right)} \end{aligned}

Therefore

lim θ 0 + r ( θ ) θ = lim θ 0 + 2 sin ( θ + π 4 ) 1 θ ( 2 + 1 sin ( θ + π 4 ) ) A 0/0 case, L’H o ˆ pital’s rule applies. = lim θ 0 + 2 cos ( θ + π 4 ) 2 + 1 sin ( θ + π 4 ) θ cos ( θ + π 4 ) Differentiate up and down w.r.t. θ . = 1 2 + 1 1 2 = 2 2 + 2 1 = 2 2 + 1 = 2 ( 2 1 ) ( 2 + 1 ) ( 2 1 ) = 2 2 \begin{aligned} \lim_{\theta \to 0^+} \frac {r(\theta)}\theta & = \lim_{\theta \to 0^+} \frac {\sqrt 2 \sin \left(\theta + \frac \pi 4 \right)-1}{\theta \left(\sqrt 2 + 1 - \sin \left(\theta + \frac \pi 4 \right)\right)} & \small \blue{\text{A 0/0 case, L'Hôpital's rule applies.}} \\ & = \lim_{\theta \to 0^+} \frac {\sqrt 2 \cos \left(\theta + \frac \pi 4 \right)}{\sqrt 2 + 1 - \sin \left(\theta + \frac \pi 4 \right)-\theta \cos \left(\theta + \frac \pi 4 \right)} & \small \blue{\text{Differentiate up and down w.r.t. }\theta.} \\ & = \frac 1{\sqrt 2+1 - \frac 1{\sqrt 2}} = \frac {\sqrt 2}{2 + \sqrt 2 - 1} = \frac {\sqrt 2}{\sqrt 2 +1} \\ & = \frac {\sqrt 2(\sqrt 2-1)}{(\sqrt2+1)(\sqrt2-1)} = \boxed{2-\sqrt 2} \end{aligned}


Reference: L'Hôpital's rule

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...